Does paying taxes generate less firm survival? An analysis from Ecuadorian service firms - Carrión, Cristian (2021)
The service sector in Ecuador constitutes one of the most important components for the Gross Domestic Product and also for the generation of employment. In recent years, according to INEC data, the contribution of the tertiary sector to GDP was approximately 60% annually; And although Ecuador has historically depended on the primary sector, companies dedicated to providing services have a majority weight in the national economy. The income tax caused has a negative sign in the general model and at the subsector level, this result differs with the expected result mainly due to the relationship of this variable with sales income. Likewise, the impact of the income tax caused depends on the size of the company, which is greater when it comes to medium-sized companies while its effect is less for small companies. Finally, a relationship different from that expected is established with respect to the level of knowledge, since the companies with greater intensity of knowledge would present a greater probability of exiting the market.